Evaluation of marginal accuracy of polyetheretherketone and zirconia copings fabricated using computer-aided design/computer-aided manufacturing technique: An in vitro study - Manish Jangade; Ranu Sharma; Nishanth A. Sudharson; Raj Jain; Shailendra Kumar Sahu; Anurag Dani (The Journal of Indian Prosthodontic Society)
Aim: The aim of this study was to compare the marginal accuracy of polyetheretherketone (PEEK) and zirconia copings fabricated using computer-aided design/computer-aided manufacturing (CAD/CAM) technology, and to assess the impact of their material properties on accuracy when produced with a 4-axis milling system under controlled conditions. Settings and Design: The study employed an in vitro design with a stainless steel die model featuring a 6 mm axial wall height, a 6-degree total occlusal convergence, and a radial shoulder finish line. Materials and Methods: Thirty stone dies were created from silicone impressions of the metal die and poured using type-IV dental stone. The dies were divided into two groups: Group-A (PEEK) copings and Group-B (zirconia) copings. All copings were fabricated using a CAD/CAM system. Vertical marginal accuracy was assessed with a stereomicroscope and image analysis software at ×20 magnification. The marginal gaP values were subjected to a student (independent) t-test for statistical analysis. Statistical Analysis Used: The statistical analysis involved a student (independent) t-test to compare the marginal gaP values between Group A (PEEK) and Group B (zirconia). Results: The mean marginal discrepancy for Group A (PEEK) and Group B (zirconia) was 92.84 μm ± 3.48 μm and 63.12 μm ± 31.47 μm, respectively. A statistically significant variation (t = 3.635, P = 0.001) between the groups was observed, indicating better marginal accuracy with zirconia copings compared to PEEK copings. Conclusion: Both PEEK and zirconia copings demonstrated vertical marginal discrepancies within the clinically acceptable limit of <120 μm. However, zirconia copings exhibited superior marginal accuracy in this in vitro study.